NIR light controlled release of caged hydrogen sulfide based on upconversion nanoparticles1. Issue 44 (4th June 2015) - Chen, Wansong; Chen, Min; Zang, Qiguang; Wang, Liqiang; Tang, Feiying; Han, Yajing; Yang, Cejun; Deng, Liu; Liu, You-Nian
<x xml:space="preserve">Abstract</x> The first near-infrared light induced H2S release platform based on upconversion nanoparticles was constructed.